Angry Women Are More Trusting: The Differential Effects of Perceived Social Distance on Trust Behavior - Zhang, Keshun; Goetz, Thomas; Chen, Fadong; Sverdlik, Anna (Frontiers in Psychology, 2021)
Accumulating evidence suggests that anger can have a strong impact on discrete trust behaviors. However, the mechanisms underlying how anger influences trust are still unclear. Based on the appraisal tendency framework, we hypothesized that perceived social distance would positively mediate the effect of anger on trust, and that gender would moderate this mediation. In Study 1, a 2 (Anger vs. Control) x 2 (Men vs. Women) factorial design was used to investigate this hypothesis. Results supported our predictions that anger drove women, but not men, to perceive smaller social distance, and thus sent more money to their counterparts in a trust game as compared to controls. In Study 2, social distance was manipulated, and a 2 (Low social distance vs. Control) x 2 (Men vs. Women) factorial design was used to critically test the causal role of the mediator, namely to examine the effect of perceived social distance on trust. Results showed that women, but not men, sent more money to their counterparts in the low social distance condition than in the control condition. Results of both studies indicate that the high certainty, higher individual control, and approach motivation associated with anger could trigger optimistic risk assessment, and thus more trust toward others in women, via perceiving smaller social distance to others.